TINJAUAN YURIDIS MENGENAI REMIX LAGU DI APLIKASI TIKTOK BERDASARKAN UU NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Nanda Jala Sena; David Tan Tan (Universitas Islam Syekh Yusuf, 2022)
TikTok is a video platform with lots of special effects and a wide selection of music. It's no secret that the songs that are used as backsound for TikTok videos are enough to make listeners addicted. In this alldigital era, especially in the music industry, various problems often occur due to advances and sophistication of technology, making it easy for everyone to access other people's works. Like now, many remixed songs from the TikTok application have appeared which rearrange and change/add lyrics outside of the original version of the music. The purpose of writing this article is to discuss the provisions of tiktok regarding the form of content that can be shared and how many remix songs are spread on tiktok and whether tiktok can be dragged into acts of copyright infringement. Keywords: TikTok; Song; Remix; Copyright